PROBLEMATICS OF THE EFFECTIVE SOVEREIGNTY: ACTION AND RETENTION OF ACTION - Мухамедієв, В. Є. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
The concept of sovereignty in modern realities is analyzed. An attempt was made to change the approach to the problematic of the criteria themselves in connection with the fact that. Sovereignty can no longer be determined only through the legal framework, because political reality began to play a major role. It is through real politics that the status and role of the state are determined. New challenges raise the question of effective sovereignty, only in this way the classical state will be able to defend its right to exist.